Harnessing and Enhancing Macrophage Phagocytosis for Cancer Therapy - Siqi Chen; Seigmund W. T. Lai; Christine E. Brown; Christine E. Brown; Mingye Feng (Frontiers in Immunology, 2021)
Cancer immunotherapy has revolutionized the paradigm for the clinical management of cancer. While FDA-approved cancer immunotherapies thus far mainly exploit the adaptive immunity for therapeutic efficacy, there is a growing appreciation for the importance of innate immunity in tumor cell surveillance and eradication. The past decade has witnessed macrophages being thrust into the spotlight as critical effectors of an innate anti-tumor response. Promising evidence from preclinical and clinical studies have established targeting macrophage phagocytosis as an effective therapeutic strategy, either alone or in combination with other therapeutic moieties. Here, we review the recent translational advances in harnessing macrophage phagocytosis as a pivotal therapeutic effort in cancer treatment. In addition, this review emphasizes phagocytosis checkpoint blockade and the use of nanoparticles as effective strategies to potentiate macrophages for phagocytosis. We also highlight chimeric antigen receptor macrophages as a next-generation therapeutic modality linking the closely intertwined innate and adaptive immunity to induce efficacious anti-tumor immune responses.